Excitation of magnetostatic spin waves in anisotropic ferromagnetic films, magnetized in arbitrary direction - Kuzovlev, Yu.E.; Mezin, N.I.; Medvedev, Yu.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
Exact analytical expressions for propagator of small-amplitude linear magnetostatic waves in ferromagnetic thin film between two antennae and their corresponding mutual impedance are obtained by solving the linearized torque equation of spin dynamics (Landau–Lifshitz equation) in magnetostatic approximation. This is done for the case of arbitrary orientation of uniform static magnetization of the film and full account for arbitrary magnetic anisotropy. The result also contains full description of the magnetostatic spin-wave spectrum.